An Analysis of Market Timing and Stock Selection Ability of Fund Managers in India - Prakash, R. P.; Basanna, Prakash (Indian Journal of Research in Capital Markets, 2016)
The concept of mutual funds emerged in India with the establishment of Unit Trust of India (UTI) in July 1964. The performance of mutual fund schemes is dependent on the right strategy adopted by fund managers in designing the portfolio. This, in turn, depends on two important skills of fund managers, that is, market timing and stock selection ability. MarketÂ timing and stock selection ability of fund managers are imperative to comprehend how well they do in attaining the desired returns targets by the investors. We set two objectives: (a) to examine stock selection abilities of fund managers and, (b) to examine market timing abilities of fund managers. For this purpose, NAVs of 80 mutual fund schemes (both growth and balanced) were considered and tested by considering two important models, Treynor & Mazuy model and Henriksson & Merton model, and tested with Durbin- Watson to correct for potential autocorrelation. The results showed that the majority of the schemes chosen for the study are statistically not significant and hence, it was proved that the fund managers do not possess stock selection ability and market timing ability. The study also found that no scheme performed better under both the measures - TM and HM models.